The Influence of Employee Skills, Coordination, and Job Description on Employee Performance: The Mediating Role of Managerial Control in the National Land Agency in Buleleng Regency - Widya Halmahe Rani; Ni Luh Eka Ayu Permoni (Jurnal Manajemen (Edisi Elektronik), 2025)
This study aims to analyze the influence of employee ability,coordination, and job description on employee performance, with controlling as a mediating variable, at the Buleleng Regency National Land Agency (BPN) Office. The research uses a quantitative approach with purposive sampling involving 66 employees who meet predetermined criteria. Data were collected through strutured questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that job description has a significant effect on controlling, and controlling has a significant effect on employee performance. Employee ability also has a proven direct effect   on   performance.   However, employee ability and coordination do not have a significant effect on controlling or on performance through controlling. Likewise, coordination and job description do not have a direct effect on employee performance. These findings emphasize the crucial role   of   managerial   controlling in linking job description clarity with employee performance outcomes. Therefore,  strengthening  the  control   system and ensuring that job descriptions are  well-defined  and  effectively   communicated  are   key  strategies  for  improving  performance in public sector organizations, particularly in the land administration domain.